Pembangunan Sistem Pemetaan Berbasis Web-Gis Untuk Analisis Potensi Usaha Di Kabupaten Malang Menggunakan Metode Analytical Hierarchy Process (AHP) (Studi Kasus: Badan Perencanaan Pembangunan Daerah Kabupaten Malang) - Ihwan Latif; Denny Sagita Rusdianto; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The choice of strategic business locations will affect the success of business activities that will be implemented. While, the people often gets some problems when they are determining the right business potential in the search location. These problems occurred in Malang Regency, when people or investors are determining potentially business areas, they don't have any consideration for the appropriate and profitable locations from existing land resources. For example, they are currently not able to get any informations about the mapping of the business potential digitally (spatial data). To solve these problems, a system that can provide geographic information as well as perform analysis for making decision about recommendations of business potential location is required. That information can be realized by utilizing Geographichs Information System (GIS) technology and Analytical Hierarchy Process (AHP) method. This system has been successfully tested using the white-box testing method for unit testing and the result is there are 6 independent-paths from Analisis Kriteria Class, 6 independent-paths from Analisis Alternatif Class, and 14 independent-paths from Ranking Class while the black-box testing method used for validation testing and the result is very good 100% (valid).